The prognostic significance of tumor-immune microenvironment in ascites of patients with high-grade serous carcinoma - Miceska, Simona (Radiology and oncology (Ljubljana), 2023)
Background: High-grade serous carcinoma (HGSC) is often associated with ascites at presentation. Our objective was to quantify immune cells (ICs) in ascites prior to any treatment was given and evaluate their impact on progression-free survival (PFS) and overall survival (OS). Patients and methods: Forty-seven patients with primary HGSC and ascites were included. Flow-cytometric analysis was performed to detect percentages of CD3+ T cells (CD4+, CD8+, Tregs, and NKT cells), B cells, NK cells (CD56brightCD16- and CD56dimCD16+ subsets), macrophages and dendritic cells (DCs). Furthermore, CD103 expression was analyzed on T cells and their subsets, while PD-1 and PD-L1 expression on all ICs. Cut-off of low and high percentages of ICs was determined by the median of variables, and correlation with PFS and OS was calculated. Results: CD3+ cells were the predominant ICs (median 51%), while the presence of other ICs was much lower (median ?10%). CD103+ expression was mostly present on CD8+, and not CD4+ cells. PD-1 was mainly expressed on CD3+ T cells (median 20%), lower expression was observed on other ICs (median ?10%). PD-L1 expression was not detected. High percentages of CD103+CD3+ T cells, PD-1+ Tregs, CD56brightCD16- NK cells, and DCs correlated with prolonged PFS and OS, while high percentages of CD8+ cells, macrophages, and PD-1+CD56brightCD16- NK cells, along with low percentages of CD4+ cells, correlated with better OS only. DCs were the only independent prognostic marker among all ICs. Conclusions: Our results highlight the potential of ascites tumor-immune microenvironment to provide additional prognostic information for HGSC patients. However, a larger patient cohort and longer follow-up are needed to confirm our finBackground: High-grade serous carcinoma (HGSC) is often associated with ascites at presentation. Our objective was to quantify immune cells (ICs) in ascites prior to any treatment was given and evaluate their impact on progression-free survival (PFS) and overall survival (OS). Patients and methods: Forty-seven patients with primary HGSC and ascites were included. Flow-cytometric analysis was performed to detect percentages of CD3+ T cells (CD4+, CD8+, Tregs, and NKT cells), B cells, NK cells (CD56brightCD16- and CD56dimCD16+ subsets), macrophages and dendritic cells (DCs). Furthermore, CD103 expression was analyzed on T cells and their subsets, while PD-1 and PD-L1 expression on all ICs. Cut-off of low and high percentages of ICs was determined by the median of variables, and correlation with PFS and OS was calculated. Results: CD3+ cells were the predominant ICs (median 51%), while the presence of other ICs was much lower (median ?10%). CD103+ expression was mostly present on CD8+, and not CD4+ cells. PD-1 was mainly expressed on CD3+ T cells (median 20%), lower expression was observed on other ICs (median ?10%). PD-L1 expression was not detected. High percentages of CD103+CD3+ T cells, PD-1+ Tregs, CD56brightCD16- NK cells, and DCs correlated with prolonged PFS and OS, while high percentages of CD8+ cells, macrophages, and PD-1+CD56brightCD16- NK cells, along with low percentages of CD4+ cells, correlated with better OS only. DCs were the only independent prognostic marker among all ICs. Conclusions: Our results highlight the potential of ascites tumor-immune microenvironment to provide additional prognostic information for HGSC patients. However, a larger patient cohort and longer follow-up are needed to confirm our findings.dings.
Keywords: biološki označevalci; high-grade serous carcinoma; immune cells; imunske celice; napovedni označevalci; prognostic markers; visoko tvegani raki